A Review of Mixed‐Effects Models of Tumor Growth and Effects of Anticancer Drug Treatment Used in Population Analysis. (7th May 2014) - Ribba, B; Holford, NH; Magni, P; Trocóniz, I; Gueorguieva, I; Girard, P; Sarr, C; Elishmereni, M; Kloft, C; Friberg, LE
Abstract : Population modeling of tumor size dynamics has recently emerged as an important tool in pharmacometric research. A series of new mixed‐effects models have been reported recently, and we present herein a synthetic view of models with published mathematical equations aimed at describing the dynamics of tumor size in cancer patients following anticancer drug treatment. This selection of models will constitute the basis for the Drug Disease Model Resources (DDMoRe) repository for models on oncology. CPT: Pharmacometrics & Systems Pharmacology (2014) 3, e113; doi:10.1038/psp.2014.12 ; advance online publication 7 May 2014